Employee stock ownership and firm exit decisions: A cross-country analysis of rank-and-file employees - Hennig, Jan C.; Ahrens, Carolin; Oehmichen, Jana; Wolff, Michael (Accounting, Organizations and Society, 2023)
While multinational firms invest large amounts of money in employee stock ownership plans (ESOPs) to reduce turnover, there is little evidence regarding ESOPs' effectiveness in retaining rank-and-file employees and none on a global scale. Building on psychological ownership (PO) arguments, we predict that a rank-and-file employee's ESOP participation will be negatively associated with a firm exit decision and that this effect will be stronger in contextual settings that are more conducive to turnover. For our analysis, we used internal data from a large multinational firm covering 190,453 rank-and-file employees and approximately 650,000 employee years. We find that ESOP participation is associated with a lower likelihood of individual firm exit decisions. We also find this effect to be more pronounced in countries with favorable labor market conditions and lower uncertainty avoidance (UA). Additional tests support our argument that PO arising from ESOP participation is particularly important for rank-and-file employees, who often only invest small amounts. Overall, our study provides cross-country evidence regarding the retention effect of ESOP participation for rank-and-file employees.